Safety and Efficacy of Scanning Ultrasound Treatment of Aged APP23 Mice - Leinenga, Gerhard; Götz, Jürgen (Frontiers in Neuroscience, 2018)
Deposition of amyloid-β (Aβ) peptide leads to amyloid plaques that together with tau deposits characterize the brains of patients with Alzheimer's disease (AD). In modelling this pathology, transgenic animals such as the APP23 strain, that expresses a mutant form of the amyloid precursor protein found in familial cases of AD, have been instrumental. In previous studies, we have shown that repeated treatments with ultrasound in a scanning mode (termed scanning ultrasound or SUS) were effective in removing Aβ and restoring memory functions, without the need for a therapeutic agent such as an Aβ antibody. Considering that age is the most important risk factor for AD, we extended this study in which the mice were only 12 months old at the time of treatment by assessing a cohort of two year-old mice. Interestingly, at this age, APP23 mice are characterized by cerebral amyloid angiopathy (CAA) and the presence of occasional microbleeds. We found that SUS in aged mice that have been exposed to four SUS sessions that were spread out over 8 weeks and analyzed 4 weeks later did not show evidence of increased CAA or microbleeds. Furthermore, amyloid was reduced as assessed by methoxy-XO4 fluorescence. In addition, plaque-associated microglia were more numerous in SUS treated mice. Together this adds to the notion that SUS may be a treatment modality for human neurodegenerative diseases.